2021
DOI: 10.1186/s12889-021-11129-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high blood pressure-health literacy, self-management behavior, self-efficacy and social support on the health-related quality of life of Kazakh hypertension patients in a low-income rural area of China: a structural equation model

Abstract: Background Health-Related Quality of Life (HRQoL) of hypertensive patients is not only affected by the disease itself but also by some subjective factors. Low health literacy is prevalent among ethnic minorities. Considering the Kazakh-Chinese people have the highest prevalence of hypertension in Xinjiang, and the High Blood Pressure-Health Literacy (HBP-HL) has not been included in the study of HRQoL. The synergistic effects and the potential mechanism HBP-HL, self-management behavior, therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
(56 reference statements)
1
13
0
Order By: Relevance
“…The patient's mastery of disease knowledge is the premise of the patient's behavior change, correct and effective health knowledge is the basis for improving patients' self-management ability, thus effectively control the disease and reduce the rate of rehospitalization [ 10 ]. The results of this study showed that the patients' total score of rehabilitation exercise knowledge, belief, and behavior was 33.02 ± 6.28 points, which was at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…The patient's mastery of disease knowledge is the premise of the patient's behavior change, correct and effective health knowledge is the basis for improving patients' self-management ability, thus effectively control the disease and reduce the rate of rehospitalization [ 10 ]. The results of this study showed that the patients' total score of rehabilitation exercise knowledge, belief, and behavior was 33.02 ± 6.28 points, which was at a low level.…”
Section: Discussionmentioning
confidence: 99%
“…By providing education using the right method, respondents will be encouraged to adhere to the treatment they are undergoing (Listiana et al, 2020). Several studies have shown that providing education about selfcare is effective in increasing compliance with hypertension sufferers to take medication, and increasing knowledge about prevention, but it has not been effective in increasing blood pressure control compliance (Delavar et al, 2020;Zhang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…P < 0.05 means a significant difference, and GraphPad Prism V5.0 was used to generate the graphs. 23 ■ RESULTS…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The experimental data were processed using SPSS18.0 software (one-way ANOVA), and they are expressed as mean ± standard deviation. P < 0.05 means a significant difference, and GraphPad Prism V5.0 was used to generate the graphs …”
Section: Methodsmentioning
confidence: 99%